Legal aspects and government policy in increasing the role of MSMEs in the Halal ecosystem [version 4; peer review: 1 approved, 2 approved with reservations] - Suartini Suartini; Sonny Zulhuda; Yusup Hidayat; Aris Machmud (F1000Research)
Background Indonesia currently could not make it to the top ten global halal due to some external and internal factors, although it is the largest Muslim country. In the external sector, the competition map is getting tougher, while internally, there are handicaps in the form of weak public awareness of competition. As a country with the largest Muslim population in the world, Indonesia can become one of the largest markets in the world. As indicated in the Global Islamic Economic Report (GIER), Indonesia is one of the top ten countries that control the Islamic economic market, yet it fails to dominate its Islamic market. Accordingly, the government needs to play a stronger role through regulatory policies to encourage the development of the Islamic economic ecosystem in Indonesia (halal value chain). The purpose of this study is to find out and analyse the existence of Micro, small, and medium enterprises (MSMEs) in Indonesia in the world’s market for Halal products and Services. Methods The researchers have conducted a form of normative juridical research with the analytical descriptive method, namely by collecting, describing, analysing, and presenting what is (das sein) and what ought to be (das sollen). Results Support from the government and stakeholders has not been optimal in improving welfare - capital access, management, and halal certification, so the existence of the global halal ecosystem has not yet impacted MSMEs’ ability to compete competitively. Conclusions The conclusion of this study shows that the quadruple helix innovation system is capable of guaranteeing the development of MSMEs in a manner to achieves a high level of competitiveness - efficiency, and effectiveness of the products and services produced.